2010
DOI: 10.1128/jcm.01737-09
|View full text |Cite
|
Sign up to set email alerts
|

Two Unusual Cases of Severe Soft Tissue Infection Caused by Streptococcus dysgalactiae subsp. equisimilis

Abstract: We present two cases of invasive infection caused by Streptococcus dysgalactiae subsp. equisimilis, one that showed rapidly developing necrotizing fasciitis in a previously healthy man and one that showed severe cellulitis and septic shock even though the bacterium possessed a mutated emm gene, predicted to encode a truncated M protein. CASE REPORTPatient 1 was a 48-year-old, previously healthy man admitted to Haukeland University Hospital in Western Norway with a fever and a rapidly spreading erythema of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
(28 reference statements)
0
15
0
1
Order By: Relevance
“…Person-to-person transmission routes of SDSE should be determined in detail by future surveillance. The prevalence of invasive SDSE infection has increased over the years elsewhere in Asia [6,36], in Europe [37][38][39][40][41][42][43], and in America [5,31,44], as well as in Japan. As for age distribution, population-based surveillance carried out by Broyles et al (n = 212) [5] found that most patients with invasive diseases (59.0%) were adults less than 65 years old, while the majority in our study (74.0%) were at least 65 years old [3].…”
Section: Emergence Of Invasive Sdse Infectionsmentioning
confidence: 99%
“…Person-to-person transmission routes of SDSE should be determined in detail by future surveillance. The prevalence of invasive SDSE infection has increased over the years elsewhere in Asia [6,36], in Europe [37][38][39][40][41][42][43], and in America [5,31,44], as well as in Japan. As for age distribution, population-based surveillance carried out by Broyles et al (n = 212) [5] found that most patients with invasive diseases (59.0%) were adults less than 65 years old, while the majority in our study (74.0%) were at least 65 years old [3].…”
Section: Emergence Of Invasive Sdse Infectionsmentioning
confidence: 99%
“…Isolates identified as GAS or GGS were further speciated based on the results of biologic tests, which were performed with use of rapid ID-32 strep (Sysmex-bioMérieux). Since SDSE may posses Lancefield A, C or G and these substantial overlaps exist between species, general phenotypic characteristics were not adequate for providing accurate identification [9,10,11]. Streptococcal infection was also confirmed by the increase in anti-streptolysin O (ASO) titers in most cases.…”
Section: Methodsmentioning
confidence: 99%
“…Other beta-hemolytic streptococci, including group B, C, and G strains, also have the ability to cause serious human illnesses, including streptococcal TSS with or without necrotizing fasciitis and myositis (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Additionally, group B streptococci are well known to cause neonatal sepsis and meningitis, and group C and G strains cause pharyngitis.…”
mentioning
confidence: 99%